PROBABILITAS PRAKTEK PEMBERIAN MAKANAN PENDAMPING AIR SUSU IBU (MP-ASI) PADA ANAK USIA 6-23 BULAN DI INDONESIA: STUDI CROSS-SECTIONAL - simbolon, demsa (JURNAL SVASTA HARENA RAFFLESIA, 2023)
The cause of the double nutritional burden problem in Indonesia is one of the reasons for giving complementary food to ASI (MP-ASI) earlier (<6 months). The practice of giving MP-ASI in several countries, including Indonesia, has not yet reached the national target and the influencing factors are unknown based on national survey data. This study aims to determine the practice of giving MP-ASI to children aged 6-23 months in Indonesia and the influencing factors based on IDHS 2017 data. Research design using a cross-sectional study. The data comes from the results of the 2017 IDHS. The population is all mothers aged 15-49 years who have children aged 6-23 months. The sample is mothers aged 15-49 years who have children aged 6-23 months of 4,985 children. Data analysis used multivariate logistic regression. The practice of giving MP-ASI according to recommendations is 55.53%. Socioeconomic status (p= 0.0001; OR=1.172), place of residence (p= 0.0001; OR=1.168), education (p= 0.002; OR= 1.126), and parity (p= 0.001; OR=0.982) are significantly related to the practice of giving MP-ASI to children aged 6-23 months in Indonesia. The most dominant factor related to the practice of giving MP-ASI is socio-economic status. The probability that the practice of giving MP-ASI is not in accordance with recommendations based on risk factors is 86%. Socioeconomic status, place of residence, education, employment, parity as determinants of the practice of giving MP-ASI to children aged 6-23 months. Need to strengthen strategies to reduce poverty and increase education levels, increase access to health services in rural areas, increase visits of pregnant women and toddlers to posyandu, and improve strategies for family planning programs.